Athletes' Self Efficacy and Competitive Anxiety: A Descriptive Study on Different Sports - Erpiyana, Dina; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi; Salsabila, Nadia Nada (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
Athletes from different sports often lack confidence in their abilities, leading to significant doubts that affect their performance in competition. Thus, it affects athletes' emotional responses to challenges in competition, including competitive anxiety. This study aims to examine the relationship between self-efficacy and competitive anxiety in university athletes. A quantitative descriptive correlational design was used in this study involving 39 university athletes aged 18-22 years from different sports. Data collection in this study used the Self-Efficacy and Competitive Anxiety questionnaires. After the data were obtained, data analysis was carried out using SPSS Version 30, including a correlation test. The study found a significant positive relationship between self-efficacy and competitive anxiety among university athletes. This is indicated by the significance value in each category (p <0.05), so it cannot be ignored. Thus, it can be concluded that self-efficacy is positively related to competitive anxiety among university athletes; therefore, the researcher suggests that coaches pay closer attention to athletes' self-efficacy